My Experience in Teaching Programmatic Advertising. (November 2019) - Li, Hairong
This article describes how a programmatic advertising course was developed and taught for undergraduate students. Depending on the resources available when the course was offered each time, different approaches were taken, which were the client–agency approach, consulting approach, and custom learning approach. The course content consisted of seven units: introduction to programmatic, programmatic ecosystem, programmatic creative, programmatic process, programmatic measurement, programmatic optimization, and programmatic future. Each unit is briefly summarized in the article, along with a sketch of course materials and final thoughts on teaching the course in the future.